2014
DOI: 10.1371/journal.pone.0096441
|View full text |Cite
|
Sign up to set email alerts
|

Sonic Hedgehog-Gli1 Signaling Pathway Regulates the Epithelial Mesenchymal Transition (EMT) by Mediating a New Target Gene, S100A4, in Pancreatic Cancer Cells

Abstract: AimsThe hedgehog signaling pathway plays an important role in EMT of pancreatic cancer cells, but the precise mechanisms remain elusive. Because S100A4 as a key EMT moleculer marker was found to be upregulated upon Gli1 in pancreatic cancer cells, we focused on the relationship between Shh-Gli1 signals and S100 genes family.MethodsOn the base of cDNA microarray data, we investigated regulating mechanism of Gli1 to some members of S100A genes family in pancreatic cancer cell lines firstly. Then, the regulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 39 publications
3
55
0
Order By: Relevance
“…Numerous lines of evidence have shown aberrant activation of the Shh signaling pathway in cancer patients and drug intervention to block the transduction has resulted in tumor shrinking and cancer cell apoptosis in numerous types of solid tumor (12)(13)(14). In vivo and in vitro, pancreatic cancer cells have a lower proliferative and a higher apoptotic rate after intervention with an Shh antagonist (15,16). Following suppression by a specific inhibitor, malignant hepatic neoplasms also display a reduction in the degree of malignancy, such as slower proliferation and higher vulnerability to chemotherapy (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous lines of evidence have shown aberrant activation of the Shh signaling pathway in cancer patients and drug intervention to block the transduction has resulted in tumor shrinking and cancer cell apoptosis in numerous types of solid tumor (12)(13)(14). In vivo and in vitro, pancreatic cancer cells have a lower proliferative and a higher apoptotic rate after intervention with an Shh antagonist (15,16). Following suppression by a specific inhibitor, malignant hepatic neoplasms also display a reduction in the degree of malignancy, such as slower proliferation and higher vulnerability to chemotherapy (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, pancreatic tumors from HNKtreated group exhibited decreased desmoplasia as confirmed by immunostaining of extracellular matrix and myofibroblast marker proteins. Expression of CXCR4 and sonic hedgehog (SHH), two known promoters of tumor growth, metastasis and desmoplasia (13)(14)(15)(16)(17), was reduced in HNK-treated pancreatic tumor xenografts and in cancer cell lines in vitro. Further biochemical studies suggested the role of nuclear factor-kappaB (NF-κB) in suppression of CXCR4 and SHH expression.…”
Section: Introductionmentioning
confidence: 99%
“…39 There are also numbers of research revealed that Curcumin has specific regulation to Hedgehog signaling pathway and EMT process 7,40,41 in several cancer cells including pancreas, colon, leukemia, prostate carcinoma and glioblastomas. 8,[42][43][44] Islam SS et al and Xu X et al 9,10 point out that the Hedgehog signaling pathway activates EMT process to promote tumorigenicity and stemness. It is potent that Tsai, C. L.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 And Curcumin could also prevent the EMT in different tumor cells. 9,10 With the interruption of EMT, Curcumin might cover the shortage of g-irradiation (induction of EMT). In this research, we had experiments on LN229 and U251 cells, which represented to be sensitive and insensitive to cytotoxic effect of g-irradiation, respectively.…”
Section: Introductionmentioning
confidence: 99%